2014
DOI: 10.1097/qai.0000000000000092
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection Deregulates the Balance Between Regulatory T Cells and IL-2–Producing CD4 T Cells by Decreasing the Expression of the IL-2 Receptor in Treg

Abstract: Indexation of regulatory T cells (Treg) to the number of activated T cells constitutes a homeostatic mechanism ensuring that T-cell expansion remains under control. However, immune hyperactivation observed in HIV-infected patients suggests a possible dysfunction of this mechanism. Here we show that the Treg/IL-2-producing cells' balance is deeply disturbed in viremic HIV-infected patients. We found a lower expression of IL-2 receptor alpha on Treg from viremic patients. We confirmed in vitro that HIV infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…We have previously demonstrated that the depletion of Treg cells seems to be mediated by the direct HIV-1-infection of the Treg cells and the consequent disturbance of their phenotype expression and function [ 9 , 18 ], which has been also confirmed by other authors [ 27 ]. Therefore, new therapeutic approaches directed to impeding the Treg HIV-1 infection and to preserving this population of cells could be of great interest in the HIV-1-infected subjects.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…We have previously demonstrated that the depletion of Treg cells seems to be mediated by the direct HIV-1-infection of the Treg cells and the consequent disturbance of their phenotype expression and function [ 9 , 18 ], which has been also confirmed by other authors [ 27 ]. Therefore, new therapeutic approaches directed to impeding the Treg HIV-1 infection and to preserving this population of cells could be of great interest in the HIV-1-infected subjects.…”
Section: Discussionsupporting
confidence: 57%
“…Treg cells were purified by sorter as previously described [ 9 , 10 ]. Then, they were identified as CD4 + CD25 + CD127 low and flow cytometry analysis of isolated Treg cells indicates that >85% were Foxp3+.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Blocking antibodies against IL-2R is in use in organ transplantation follow-up treatment to control the numbers of activated anti-transplant T or B cells.…”
Section: Therapeutic Optionsmentioning
confidence: 99%
“…Also, reduction in the expression of IL-2R α in Treg cells was observed in HIV-infected subjects with high viral load. This alteration could result in reduced Treg cells capacity function in these individuals, considering that the homeostatic role of this cells depends on IL-2 and the expression of IL-2R α at the cell surface [ 37 ].…”
Section: The Role Of Treg Cells On Hiv Infectionmentioning
confidence: 99%